Ascent velocity and dynamics of the Fiumicino mud eruption, Rome, Italy. Issue 15 (4th August 2015) - Vona, A.; Giordano, G.; De Benedetti, A. A.; D'Ambrosio, R.; Romano, C.; Manga, M.
Abstract In August 2013 drilling triggered the eruption of mud near the international airport of Fiumicino (Rome, Italy). We monitored the evolution of the eruption and collected samples for laboratory characterization of physicochemical and rheological properties. Over time, muds show a progressive dilution with water; the rheology is typical of pseudoplastic fluids, with a small yield stress that decreases as mud density decreases. The eruption, while not naturally triggered, shares several similarities with natural mud volcanoes, including mud componentry, grain‐size distribution, gas discharge, and mud rheology. We use the size of large ballistic fragments ejected from the vent along with mud rheology to compute a minimum ascent velocity of the mud. Computed values are consistent with in situ measurements of gas phase velocities, confirming that the stratigraphic record of mud eruptions can be quantitatively used to infer eruption history and ascent rates and hence to assess (or reassess) mud eruption hazards.